An Efficient Approach on Data Security with Cloud Computing Environment: A Comprehensive Research (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
this paper discusses the data security in cloud computing. It is a study of data inthe cloud and aspects related to it concerning security. As we all know Cloud computing is anemerging domain and security of the data must be protected over the network. Cloudcomputing is used by many of the organizations for storing the huge amount of data on theclouds. Therefore, there is need to secure the data which may in the form of text, audio, video,etc. There are numerous algorithms designed by the researchers for securing the data on thecloud.The paper will go in to details of data protection methods and approaches used throughout theworld to ensure maximum data protection by reducing risks and threats.